Selenium Status in Patients Receiving Short-Term Parenteral Nutrition: Frequency of Deficiency and Response to a Standard Supplementation Regimen. (23rd September 2013) - Walsh, Julia; Karanjia, Nariman D.; Taylor, Andrew; Livingstone, Callum
Abstract : Background . This study aimed to determine the prevalence and correlates of Se deficiency in patients referred for parenteral nutrition (PN) and to assess the response to a standard supplementation regimen. Methods. Adult patients (53) were recruited prior to commencing a PN regimen delivering 32 µg (0.4 µmol) Se per 24–36 h. Serum Se concentrations were measured before and daily during PN. Results . At baseline 49 (92%) patients had serum Se concentrations below the reference range (0.9–1.65 μ mol/L). Se concentrations climbed during PN from 0.49 ± 0.23 (mean ± SD) to 0.57 ± 0.22 μ mol/L (P < 0.05 ), but in 48 (91%) patients the concentrations remained low at post-PN. Taking a Se concentration below 0.6 μ mol/L as indicative of depletion in the presence of an acute phase response (APR), 37 (70%) patients had Se depletion at baseline and in 27 (51%), levels remained low at post-PN. Baseline serum Se predicted the length of hospital stay (r = - 0.36, P < 0.05 ). Increased "malnutrition universal screening tool" score predicted low Se (r = - 0.93, P < 0.05 ). Conclusions . Patients referred for PN have a high prevalence of Se deficiency, even when the APR is taken into account. Se supplementation of 32 µg Se per 24–36 h is insufficient for most patients. Baseline serum Se may have prognostic value.